(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND Nutritional factors play an important role in the regulation of blood pressure and in the development of hypertension. In this analysis, we explored the associations of 24-hour urinary Na+, K+ and urea excretion with blood pressure levels and the risk of hypertension in the Swiss population, taking regional linguistic differences into account. METHODS The Swiss Survey on Salt is a population based cross-sectional study that included 1336 subjects from the three main linguistic regions (French, German and Italian) of Switzerland. Blood pressure was measured with a validated oscillometric Omron HEM 907 device. Hypertension was defined as current antihypertensive treatment or a mean systolic blood pressure >140 mm Hg and/or diastolic >90 mm Hg, based on eight blood pressure measurements performed at two visits. Na+, K+ and urea excretion were assessed in 24-hour urine collections. We use multiple logistic/linear regressions to explore the associations of urine Na+, K+ and urea with blood pressure / hypertension, taking into account potential confounders and effect modifiers. RESULTS The prevalence of hypertension was 30%, 26% and 17% in the German-, French- and Italian- speaking regions respectively, (p-value across regions <0.001). In the Swiss adult population, besides age, sex, and body mass index, urinary Na+ excretion was positively associated with systolic blood pressure and hypertension. Urinary K+ excretion tended to be negatively associated with blood pressure but this was not significant (p = 0.08). Hypertensive people had a higher 24-hour urinary Na+/K+ ratio than normotensive people (p = 0.003). Urinary urea excretion was associated with neither blood pressure nor hypertension. Participants from the German-speaking region had a higher likelihood of having a high systolic blood pressure. CONCLUSIONS We confirm a high prevalence of elevated blood pressure in Swiss adults, including regional differences. In Switzerland, urinary Na+ excretion is associated positively with blood pressure and hypertension, independently of urinary K+ and urea excretion. The observed differences in blood pressure levels across linguistic regions are independent of the urinary Na+, K+ and urea excretion.